ANALYSIS OF SOCIAL MEDIA MARKETING ACTIVITIES ON CUSTOMER RESPONSE THROUGH BRAND EQUITY ON DEAR ME BEAUTY - Dhiya nabilah; Yulia Nur Hasanah (Universitas Trisakti, 2021)
Purpose -This study analyzes the effect of social media marketing activities on customer response through brand equity in Dear Me beauty. A survey was conducted with 100 respondents who participated in and used Dear me beauty products.Design/Methodology/Approach-The method used in this research is quantitative with descriptive and casual research. The sampling technique used is non-probability sampling with purposive sampling and multiple regression analysis with 100 respondents.Findings - Based on the results of descriptive analysis, social media marketing activities and brand equity are included in the very good category. Meanwhile, consumer responses are in a good category. The results show that social media marketing influences brand equity and consumer response. Furthermore, brand equity influences consumer response. Lastly, social media marketing influences consumer response through brand equity.Value-This research uses different theories such as Kotler & Keller's theory of brand equity dimensions.